Facets of Facebook Use and Users - Knautz, Kathrin; S. Katsiaryna, Baran (De Gruyter, 2016)
The debate on Facebook raises questions about the use and users of this information service. This collected volume gathers a broad spectrum of social science and information science articles about Facebook.Facebook has many facets, and we just look forward above all to the use and users. The facet of users has sub-facets, such as different age, sex, and culture. The facet of use consists of sub-facets of privacy behavior after the Snowden affair, dealing with friends, unfriending and becoming unfriended on Facebook, and possible Facebook addiction. We also consider Facebook as a source for local temporary history and respond to acceptance and quality perceptions of this social network service, as well. This book brings together all the contributions of research facets on Facebook. It is a much needed compilation written by leading scholars in the fields of investigation of the impact of Web 2.0. The target groups are social media researchers, information scientists and social scientists, and also all those who take to Facebook topics.